Content-based publish/subscribe communication model between Iot devices in smart city environment - Öztürk, Fulya; Özdemir, Ayşe Meliha (My University, 2019)
In recent years the population of the cities has been increasing the getting over half of the whole world population. These peoples are facing with some security and infrastructural needs. Some of these needs can be met with the use of some smart technologies such as Internet of Things Devices (IoT) with different types of sensors. Coordination and communication of these devices are very critical for enabling the digital solutions in a secure and comfortable city life. However, due to the restricted ability of these devices, setting up a flexible communication platform is a very challenging issue. In this paper for setting up the physical security of smart homes/buildings, a content-based publish-subscribe model is proposed by the use of wireless sensor network nodes in the critical environment. Due to the energy constraint of the devices, the broadcasting feature of the wireless communication is not used, instead of this a peer to a communication according to the content of the message is preferred. Experimental results showed that the proposed communication model can be applicable for smart city environments.
Keywords: Content-Based Notification; Publish/Subscribe; Smart City; Smart Home